PENGATURAN PENGAKUAN KEBERAGAMAN SUMBER HUKUM DALAM MASYARAKAT MULTIKULTUR MELALUI FILSAFAT HUKUM PLURALISME - Puri Rahayu, Danik; Estu Bagijo, Himawan (Jurnal Magister Hukum Perspektif, 2024)
A multicultural society with a variety of legal sources used requires a legal philosophy of pluralism. However, in Indonesia the use of pluralist legal philosophy still leaves problems related to its application and implications. This article discusses the issue of the application and implications of pluralist legal philosophy in Indonesia. This type of normative juridical research, with a qualitative approach and analytical descriptive analysis. Research results: (1) the application of the legal concept of pluralism in Indonesia requires an approach that is inclusive, participatory, and based on recognition of various existing legal sources. This step is important in achieving legal justice and balance between various interests in a multicultural society. (2) Overall, the application of the legal philosophy of pluralism has significant implications for legal certainty, inclusiveness and conflict resolution in a heterogeneous society. By recognizing and respecting the plurality of legal norms, society can build a more inclusive, fair and sustainable legal system that strengthens social peace and justice. Key words: diversity of legal sources, multicultural society, legal philosophy of pluralism